Mutating both relA and spoT of enteropathogenic Escherichia coli E2348/69 attenuates its virulence and induces interleukin 6 in vivo - Lee, Jun Bong; Kim, Se Kye; Han, Dalmuri; Yoon, Jang Won (Frontiers in Microbiology, 2023)
Here, we report for the first time that disrupting both relA and spoT genes in enteropathogenic Escherichia coli E2348/69 can attenuate its virulence and significantly induce interleukin 6 (IL-6) in vivo. Our experimental analyses demonstrated that an E2348/69 ΔrelAΔspoT double mutant strain derepressed the expression of type IV bundle forming pilus (BFP) and repressed the expression of glutamate decarboxylase (GAD) and locus of enterocyte effacement (LEE). Whole genome-scale transcriptomic analysis revealed that 1564 EPEC genes were differentially expressed in the ΔrelAΔspoT double mutant strain (cut-off > two-fold). Such depletion of relA and spoT attenuated the virulence of E2348/69 in a Caenorhabditis elegans infection model. Surprisingly, IL-6 was highly induced in porcine macrophages infected with the ΔrelAΔspoT double mutant strain compared to those with its wildtype strain. Coinciding with these in vitro results, in vivo murine peritoneal challenge assays showed high increase of IL-6 and improved bacterial clearance in response to infection by the ΔrelAΔspoT double mutant strain. Taken together, our data suggest that relA and spoT play an essential role in regulating biological processes during EPEC pathogenesis and that their depletion can affect host immune responses by inducing IL-6.